Intrinsic and Extrinsic Motivation in Second Language Acquisition (Comprehensive Journal of Science, 2026)
Motivation known to be one of the most significant determinants of success in Second Language Acquisition (SLA). It influences the effort learners put in and the quality of their engagement and learning outcomes. Early SLA research viewed motivation as a psychological trait within the individual, separating intrinsic and extrinsic factors. However, more recent developments in educational psychology and applied linguistics emphasise learner autonomy, determination, identity and emotion, along with the influence of their social environment. Therefore, this scoping review examines intrinsic and extrinsic motivation within SLA, from early socio-psychological frameworks to contemporary approaches. It includes Self-Determination Theory, sociocultural frameworks and theories of identity. Recent research conducted by scholars such as Ryan and Deci (2017), Noels (2020), Darvin and Norton (2021), Mercer and Dornyei (2020) and Hiver and Al-Hoorie (2020) shows that motivation within learning environments is variable, rather than a fixed characteristic. In fact, intrinsic and extrinsic motivations change and interact continuously as learners deal with changing contexts, develop their identities and engage in active participation. Therefore, teaching must support the individual while creating an inclusive and emotionally supportive learning environment that fosters internal and extrinsic motivation.
Keywords: Second Language Acquisition (SLA), Intrinsic motivation , Extrinsic motivation , learnin